A journey without a roadmap: A hermeneutic phenomenology of parenting children with autism spectrum disorder - Kayode Olutayo Adeniran; Stephen Ayoade Fadare; Sheree G. Ganzon; Alleina Pat Basa Calliten (Orapuh, Inc., 2024)
Introduction Parents of children with Autism Spectrum Disorder (ASD) often face heightened levels of stress and health challenges compared to parents of neurotypical children. Purpose This study aimed to explore the experiences of parents of children with ASD in Dagupan City, The Philippines. Methods Thestudy used a hermeneutic phenomenology approach to deeply examine the experiences of parents of autistic children, using the themes of the poem, "A Journey Without a Road Map." A total of 11 parents participated in the study, which was conducted using face-to-face interviews following a specific interview protocol. The researchers also observed the participants' body movements, gestures, and facial expressions to study underlying emotions. Results Four major themes from "A Journey Without a Road Map" emerged from this study, representing the systematic progression of the experiences of parents of ASD children from diagnosis to daily living. The themes are blessing and burden, traveling on a rocky road, keeping on course in uncharted territory, and pleasures in the blind journey. The researchers made extrapolations by interpreting the parents' expressions through thorough observation of their body movements, gestures, and facial expressions. Researchers had direct encounters with some parents of ASD over time, and the challenges they face daily are undeniable. They experience situations that require extra strength, devotion, and commitment, and face circumstances that test their ability to adapt and live like every other parent. Conclusion There is a need for the government or other concerned institutions to sensitize the general public about autism spectrum disorder, sustain this initiative, and establish a functional network of support groups for parents with autistic children. In addition, the process of gradually integrating ASD children into the society by ensuring they are trained and supported to perform certain jobs has proven to be effective in alleviating the burdens and distress of the parents.